How Far Do the Complaints of Patients with Parkinson's Disease Reflect Motor Fluctuation? Quantitative Analysis Using a Portable Gait Rhythmogram. (13th December 2012) - Utsumi, Hiroya; Terashi, Hiroo; Ishimura, Yohei; Takazawa, Tomoko; Okuma, Yasuyuki; Yoneyama, Mitsuru; Mitoma, Hiroshi
Abstract : In advanced-stage Parkinson's disease (PD), motor fluctuation is a frequent and disabling problem. Assessment of motor fluctuation depends on patient's subjective self-statement. We examined whether the subjective fluctuation matched the objective motor fluctuation defined by gait disorders. Using a new device, the portable gait rhythmogram, we recorded gait cadence and acceleration continuously over the 24-hour period in 54 patients with PD and 17 normal controls, for the quantitative evaluation of motor fluctuation. The patients were asked to estimate motor fluctuation every hour. In 44 of 54 patients, changes in the cadence were associated with simultaneous changes in acceleration. We examined the subjective fluctuation in these 44 patients who were confirmed to have motor fluctuation. Nineteen (82.7%) of 23 patients who felt no fluctuation showed distinct gait disorders. During off time, they walked with marked short or bradykinetic stepping. No matching changes were observed in either the cadence or acceleration in 11 (52.4%) of 21 patients who perceived motor fluctuation. No synchronization was noted in 30 (68.2%) of the 44 patients, between the times of subjectively assessed motor fluctuation and those of quantitative analysis of gait disorder. This discrepancy suggests that the objective continuous recording of the cadence and acceleration is necessary to understand motor fluctuation.